Analisis Risiko Kecelakaan Kerja Menggunakan Metode JSA dan HIARO di Departemen Energy Center PT. Indo Bharat Rayon - Nopiasadi, Muhamad Nugrah; Kusuma, Bintang Nidia; Akbar, Muhammad Ali (Fakultas Teknik Universitas Tulang Bawang, 2025)
This study aims to analyze the potential risks of workplace accidents in the Energy Center Department of PT. Indo Bharat Rayon using the Job Safety Analysis (JSA) and Hazard Identification Assessment of Risk and Opportunities (HIARO) methods. The research identifies the risks faced by employees, assesses the impact of these risks, and provides appropriate control recommendations. The research methodology involves collecting workplace accident data, conducting risk analysis using JSA and HIARO, and assessing risks before and after the implementation of controls. The results show that high-level risks were reduced from 1 to 0, and medium-level risks from 48 to 0 after the controls were applied. The remaining risks were categorized as low risks, which do not require immediate action. The recommended risk controls include elimination, substitution, engineering controls, administrative controls, and the use of personal protective equipment. The implementation of safety culture programs, such as the Safety Program and Job Safety Training, is also suggested to enhance workplace safety. This study provides benefits to the company by identifying and reducing workplace accident risks, and to researchers and universities by increasing knowledge and offering practical references on workplace safety. Keywords: HIARO, JSA, Occupational Accident Risk, OHS, Risk Control